How to effectively assess the impact of non-lethal weapons as intermediate force capabilities - Romita Grocholski, Krista; Savitz, Scott; Wong, Jonathan P.; Litterer, Sydney; Khan, Raza; Cooper, Monika (RAND, National Defense Research Institute, 2022)
The U.S Department of Defense (DoD) needs to be able to assess the tactical, operational, and strategic impact of non-lethal weapons (NLWs) to inform development of these systems, how and when they should be used, and their integration into overall DoD capabilities. Examples of NLWs include acoustic hailers, laser dazzlers, flash-bang grenades, blunt-impact munitions (e.g., rubber bullets), tasers, pepper balls, the Active Denial System (ADS) that emits millimeter-wave energy to cause a temporary heating sensation, microwave-emitting technologies that disable vehicles and vessels, and vessel-stopping technologies that entangle or foul propellers. NLWs are a subset of Intermediate Force Capabilities (IFCs). IFC is a non-doctrinal term that encompasses NLWs and a variety of technologies that cause less-than-lethal effects. By constraining other parties' courses of action without inflicting lethal force, NLWs can help to achieve military ends while avoiding collateral damage. This report describes how the tactical, operational, and strategic impact of NLWs can be characterized by linking the activities they perform with direct outputs, higher-level outcomes, and departmentwide strategic goals. It also provides sets of metrics that can be used to evaluate those activities, outputs, and outcomes. The identification and characterization of the metrics also lay the groundwork for data collection that can be used to further evaluate the impact of NLWs at multiple levels, which, in turn, can shape their usage in ways that enhance their contributions to DoD effectiveness. Interview-based insights regarding NLWs can also shape how this information is used to influence future development and usage of these systems.
"Prepared for the Joint Intermediate Force Capabilities Office" -- Titelseite unten
Keywords: USA -- Department of Defense; Nichttödliche Waffe; Evaluation; Nonlethal weapons / United States / Evaluation; Strategy; Tactics; United States / Armed Forces / Weapons systems; Armes non meurtrières / États-Unis / Évaluation; Stratégie; Tactique militaire; Armed Forces / Weapons systems; United States